LAILATUL QADAR DALAM PERSPEKTIF AHMAD AL-SHAWI : (Studi Kitab Hasyiah 'Ala Tafsir al-Jalalain) - Luthfi, Hikmatul (Al-Fath, 2022)
The book Hashiyah 'ala Tafsir al-Jalalain by Ahmad al-Shawi is one of the most popular tafsir books in Indonesia, while Lailatulqadar is a night that is the favorite of the Muslim community every year. This article discusses lailatulqadar according to Ahmad al-Shawi in his interpretation including time, indicators and practices. The results of the research show that with regard to time, indicators, and lailatulqadar practices, al-Shawi not only explains in full the opinions of various scholars, both fiqh, hadith, and Sufism in a naqli manner, but also explains tajribi (experience) and is supported by history. from the scholars. The Tajribi aspect has a Sufistic character, this is possible because al-Shawi is a Sufi expert with a khalwatiyya tradition.